Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Konsumen Pada Wedding Organizer Syadalli Production Di Bojongsari Depok - Habibullah Lubis, Muhammad; sulaiman Anhary, Agus (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Abstrak. This research aims to determine the influence of service quality and price on consumer satisfaction at Wedding Organizer Syadalli Production in Bojongsari Depok, both partially and simultaneously. The method used is quantitative methods, the research sample is 95 respondents. Data analysis methods used in research include instrument tests consisting of validity tests, reliability tests, classical assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, correlation coefficients, coefficient of determination tests, hypothesis tests consisting of partial t test and simultaneous f test. The research results show that service quality has an influence on consumer satisfaction with a calculated t value > t table or (11.516 > 1.985) and a significance value of 0.000 < 0.05. Thus, Ho1 is rejected and H1 is accepted. Price has a positive and significant influence on consumer satisfaction with a calculated t value > t table or (11.428 > 1.985) and a significance value of 0.000 < 0.05. Thus, Ho2 is rejected and H2 is accepted. Service quality and price have a positive and significant influence on consumer satisfaction with a calculated F value > F table or (78.638 > 3.090) and a significance value of 0.000 < 0.05. Thus, Ho3 is rejected and H3 is accepted. The result of the R-square value (coefficient of determination) is 0.631, it can be concluded that the service quality and price variables together have an influential contribution to the consumer satisfaction variable of 63.1%, while the remaining 36.9% is influenced by other factors or variables that are not researched Keywords: Service quality, price, consumer satisfaction